A bilayered two-dimensional hybrid perovskite with a cage-templated secondary cation for high efficiency photodetection. Issue 4 (18th January 2022) - Tang, Liwei; Chen, Huaixi; Ma, Yu; Liu, Yi; Hua, Lina; Lu, Lei; Wang, Beibei; Han, Shiguo; Sun, Zhihua; Luo, Junhua
Abstract : A novel two-dimensional hybrid perovskite (IA)2 (DMA)Pb2 Br7 was obtained by introducing a large secondary cation DMA + into the PbBr6 framework. A highly efficient array photodetector has been assembled using its crystal. Abstract : Two-dimensional (2D) multilayered hybrid perovskites adopting intrinsic quantum-well structures have shown great application potential in the field of optoelectronics. Despite extensive studies, candidate perovskites composed of cage-templated secondary ammonium cations are quite scarce, hindering their application in high efficiency devices. Here, a new 2D hybrid perovskite (IA)2 (DMA)Pb2 Br7 (1, IA + = isoamylammonium and DMA + = dimethylammonium) was synthesised, in which the inorganic bilayered frameworks are templated by secondary organic DMA + cations in the perovskite cavities. This structural characteristic is distinct from the homologues containing monovalent cations. An alternative array of organic spacing bilayers and inorganic perovskite sheets forms its quantum-well motif, which leads to intriguing physical properties. Consequently, the fabricated crystal-based array detector exhibits highly efficient photodetection behaviors, including a low dark current (∼20 pA), large responsivity (∼110 mA W −1 ) and high detectivity (∼2.8 × 10 11 Jones). These merits are related to the in-plane photoactivity of the perovskite sheets and low dark current of the insulated organic spacing bilayers. Besides, our photodetector also enables a response to polarized light with a dichromatic ratio of ∼1.15. These findings pave the way to design new photoactive hybrid perovskites and reveal their potential for application in high-performance optoelectronic devices.